EMPOWERING WOMEN'S COFFEE HARVESTING GROUPS IN UTILIZING COFFEE SKIN WASTE INTO PRODUCTS WITH ECONOMIC VALUE IN BENER MERIAH REGENCY - Faoeza Hafiz Saragih; Risky Ridha; Siti Komariyah (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Currently, most coffee processing is limited to the use of coffee beans. Coffee waste production accounts for approximately 72% of the weight of the fresh fruit and has not been optimally utilised. In Bener Meriah Regency, women engage in harvesting activities as a means of generating income for their families. With the formation of this group, it is hoped that this group of women harvesters will not only carry out harvesting activities but can utilize unused coffee skin waste and can be used to create items of high economic value. This community service activity will be carried out in Kenine Village, Timang Gajah District, Bener Meriah Regency. The target output to be achieved is increasing partner awareness to become entrepreneurs and have the skills to produce products such as tea, fertiliser and fish pellets from coffee skin waste.